The effect of using additional and informational feedback in learning and achieving the effectiveness of racing (Journal of the College of Basic Education, 2022)
Impact of the use of feedback and additional media in learning and completion of the effectiveness of walking races Tkamin importance of research in the use of feedback in physical education lesson to effectively learn the effectiveness of walking, which is one of the events with a technique of higher because of its phases of different art to all parts of the body, while the goals of research to know the impact of nutrition irreversibility in learning and improve the level of performance art to the effectiveness of walking to the research sample , and the researcher used the experimental method, the sample consisted students junior high love, and numbered (30) students, as it consisted of three groups, were chosen randomly, were testing tribal dimensional sample search, and was the most important conclusions there is an important role for feedback and additional information on the Although different use in the improvement of the effectiveness of the process of learning to walk, as well as improve the level of achievement of the effectiveness of digital walking